Emergency unit and disaster preparedness: A study of military hospitals in Saudi Arabia - Alotaibi, Yasir M (Division of Emergency Medicine, 2022)
Background: The objective of this study is to evaluate the emergency and disaster preparedness of military hospital emergency services, and to further, identify strategies for improvement in disaster preparedness and response. Saudi Arabia is prone to various man-made and natural disasters. Among these is the event of the annual pilgrimage termed Hajj, which annually presents the risk of overcrowding. Many of these disasters have resulted in mass casualties. Consequently, there has been increased emphasis on planning by disaster experts to establish and maintain an organized preparation for a wide range of emergencies. Emergency Medical Services (EMS) play a vital role in disaster management. Both pre-hospital EMS and in hospital emergency services are considered inefficient and inadequately prepared in disaster response and management. Most importantly, there is limited data on emergency care (EMS and hospital-based) disaster preparedness and responses in Saudi Arabia. Methods: We undertook a prospective cross-sectional, descriptive survey-based assessment of disaster preparedness. The research focused on collecting and analysing data through quantitative methods. To review the standard operating procedures (SOP), we sought all disaster plans and SOPs from management and emergency unit leadership at each of the 3 Medical Services Directorate (MSD) hospitals. We then undertook a questionnaire assessment, gathering quantitative data using close-ended questions and open-ended commentary surrounding a hospital's disaster response operating procedures. Results: We found a wide variability in the hospitals across the 22 themes in the survey. Most hospital emergency units have a good to excellent disaster plan. There were, however, concerns with the departmental standards with Radiology, Occupational Health, Critical Care, Respiratory Therapy, Pastoral Counselling, and provision made for the preservation of forensic evidence. Internal traffic flow and control issues presented relate to elevators manned and its prioritized usage. It is found that the area demarcated for media liaison needs improvement. Reception of casualties also needs attention and finally, relocation of patients and staff needs prioritisation. Conclusion: The study has highlighted several strengths in facility disaster preparedness and further shared the need for rigorous efforts required to improve the situation at some facilities. In general, most hospitals were found to have a good disaster management plan in place, however, a few covered all the recommended areas in sufficient detail.